Cyclophilin A is a ligand for RAGE in thrombo-inflammation - Seizer, Peter; von Ungern-Sternberg, Saskia N I; Haug, Verena; Dicenta, Valerie; Rosa, Annabelle; Butt, Elke; Nöthel, Moritz; Rohlfing, Anne-Katrin; Sigle, Manuel; Nawroth, Peter Paul; Nussbaum, Claudia; Sperandio, Markus; et al. (Cardiovascular research, 2024)
Cyclophilin A (CyPA) induces leucocyte recruitment and platelet activation upon release into the extracellular space. Extracellular CyPA therefore plays a critical role in immuno-inflammatory responses in tissue injury and thrombosis upon platelet activation. To date, CD147 (EMMPRIN) has been described as the primary receptor mediating extracellular effects of CyPA in platelets and leucocytes. The receptor for advanced glycation end products (RAGE) shares inflammatory and prothrombotic properties and has also been found to have similar ligands as CD147. In this study, we investigated the role of RAGE as a previously unknown interaction partner for CyPA.Confocal imaging, proximity ligation, co-immunoprecipitation, and atomic force microscopy were performed and demonstrated an interaction of CyPA with RAGE on the cell surface. Static and dynamic cell adhesion and chemotaxis assays towards extracellular CyPA using human leucocytes and leucocytes from RAGE-deficient Ager−/− mice were conducted. Inhibition of RAGE abrogated CyPA-induced effects on leucocyte adhesion and chemotaxis in vitro. Accordingly, Ager−/− mice showed reduced leucocyte recruitment and endothelial adhesion towards CyPA in vivo. In wild-type mice, we observed a downregulation of RAGE on leucocytes when endogenous extracellular CyPA was reduced. We furthermore evaluated the role of RAGE for platelet activation and thrombus formation upon CyPA stimulation. CyPA-induced activation of platelets was found to be dependent on RAGE, as inhibition of RAGE, as well as platelets from Ager−/− mice showed a diminished activation and thrombus formation upon CyPA stimulation. CyPA-induced signalling through RAGE was found to involve central signalling pathways including the adaptor protein MyD88, intracellular Ca2+ signalling, and NF-κB activation.We propose RAGE as a hitherto unknown receptor for CyPA mediating leucocyte as well as platelet activation. The CyPA-RAGE interaction thus represents a novel mechanism in thrombo-inflammation.